Shall We Escape Analogy - Rosmarie Waldrop (Studies in 20th & 21st Century Literature, 1989)
Claude Royet-Journoud's and Anne-Marie Albiach's work can be read as manifestos against metaphor (relation by similarity, the vertical selection axis of the speech act) with which poetry has long been identified. Whereas Royet-Joumoud takes as his theme metaphor in the largest sense (including, finally, all representation that is based on analogy), Albiach's "Enigme" dramatizes the loss of the vertical dimension through, ironically, a metaphor: the fall of a body. Formally, both stress as alternative the horizontal axis of combination (especially the spatial articulation on the page) and the implied view that the world is constructed by language, that it does not exist prior to it (waiting to be represented or expressed).
Keywords: Claude Royet-Journoud; Anne-Marie Albiach; manifesto; metaphor; speech act; poetry; French poetry; Enigme; space; spacial; language; representation; expression